2016
DOI: 10.4103/0189-6725.194673
|View full text |Cite
|
Sign up to set email alerts
|

Our experience of proximal hypospadias repair using the Cloutier–Bracka technique at the Gynaeco-Obstetric and Paediatric Hospital, Yaounde-Cameroon

Abstract: Background:In parts of Africa, routine circumcision is practised and sometimes even on children with hypospadias. The lack of preputial foreskin renders urethroplasty more difficult and often requires to use of a mucosal graft as described by Bracka.Objective:The authors describe their experience of hypospadias repair using Bracka's technique.Materials and Methods:Over a period of 5 years, 100 cases of proximal hypospadias were operated in our institution. All patients aged 0–18 years who had already been circ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…In another study by Faustin Felicien used Bracka 1 in 12 patients where he found 3 patients with complication which are (25%). 11 Sakr 12 had researched that in Bracka 1 he found graft swelling in 6 patients (26.9%) skin echimosis n=2 (12.5%) and graft loss was two (12.5%), while in our study wound infection in Brocka 1 was (2.5%) and in Blair-Byar's it was (5%). Sadegi 9 studied Bracka compared with Duckett and declared Bracka has less complication versus with Duckett; 8.1% in Bracka and 26.9% in the Duckett, while in our study uneventful surgery was in Bracka I was (92.5%) and in Blair-Byar's it was (90%).…”
Section: Discussionsupporting
confidence: 42%
“…In another study by Faustin Felicien used Bracka 1 in 12 patients where he found 3 patients with complication which are (25%). 11 Sakr 12 had researched that in Bracka 1 he found graft swelling in 6 patients (26.9%) skin echimosis n=2 (12.5%) and graft loss was two (12.5%), while in our study wound infection in Brocka 1 was (2.5%) and in Blair-Byar's it was (5%). Sadegi 9 studied Bracka compared with Duckett and declared Bracka has less complication versus with Duckett; 8.1% in Bracka and 26.9% in the Duckett, while in our study uneventful surgery was in Bracka I was (92.5%) and in Blair-Byar's it was (90%).…”
Section: Discussionsupporting
confidence: 42%
“…They concluded that the rate of meatal stenosis is much lower when the graft is taken from the buccal mucosa. 10 In another study conducted by Price et al 7 the mean meatal stenosis rate was 1.2%. In contrast, other series have shown a surprisingly high rate of meatal stenosis, ranging from 6 to 20%.…”
Section: Disscusionmentioning
confidence: 90%
“…Poor outcomes from children who have previously left their community to seek surgical care may lead to a belief in the futility of seeking help with similar conditions; this undermines the healthcare system especially when local practitioners work outside their level of expertise. A common illustration is the performance of community circumcision, where a clinically significant hypospadias is present, leading to more challenging reconstruction with higher complication and failure rates [8].…”
Section: First Delaysmentioning
confidence: 99%
“…Additionally, the outcome may be affected by prior circumcision in the community, which may compromise the tissue available to reconstruct severe hypospadias [32], whilst minor degrees of this condition will go largely untreated. Proximal hypospadias may require a Bracka-type staged hypospadias technique using autologous buccal mucosa, and the skill to perform it [8]. Complications following, or failure of, hypospadias repair by surgeons operating outside their normal skill set means parents may often be reluctant to bring their children forward for surgery.…”
Section: Hypospadiasmentioning
confidence: 99%